Tinjauan Hukum Islam Terhadap Jual Beli Online Di www.kaskus.co.id - Dewim Purnama, Ahmad; , Drs. Harun M.H; , Bapak Drs. Syarafudin HZ, M.Ag (2015)
The research based on spread of online trading on internet world which often called "Online Trading (Sell and buy by online system)". www.kaskus.co.id is one of online forum provides online market for sellers and buyers (traders) named Forum Jual Beli. Due to the object of trade and its transaction method have a lot varieties, the research was started by using Islamic law's point of view. This research used desktop study method. Some articles, writings, and books related to online trading, fikih muamalah (Islamic Trading Law) and online market on www.kaskus.co.id were used for solve the problem of the research. The problem of research is "Did the trade on www.kaskus.co.id fulfill by its pillars and requirements or not?". After reviewed, looked from Islamic trading pillars and requirements, there were cases which the requirements and the pillars were incomplete. For example, Blackberry trade scam committed by Hafid Hasan as seller. The object which sold didn't hand over to the buyer after Hafid Hasan has got paid for the blackberry unit, gambling online services and porn video sellers. Hence, those trading were prohibited. Next, the trade on www.kaskus.co.id contains obscurity or garar because the most of traders are using salam system and indirectly trading, hence, it would be used for scam. From the obscurity of trading agreement, trader's backrgounds, and the object's identity.